ChemInform Abstract: Vacancy‐Mediated Processes in the Oxidation of CO on PdO(101). Issue 32 (August 2015) - Weaver, Jason F.; Zhang, Feng; Pan, Li; Li, Tao; Asthagiri, Aravind
Abstract Review: 21 refs.